Anaerobic biogas formation from crops' agricultural residues – Modeling investigations. (September 2022) - Scherzinger, Marvin; Kaltschmitt, Martin; Elbanhawy, Amr Y.
Graphical abstract: Highlights: Biogas production was modelled based on kinetic Gompertz-Models. The model can be applied to other substrates using relatively simple batch studies. Indications regarding optimal operation of small-scale biogas plants are supplied. A complete feed analysis of various biogenic residues from Egypt is presented. Abstract: The cultivation of field crops necessarily produces large quantities of organic residues, which could be used for the production of biogas. However, this is only successfully possible if the operators of such biogas plants have sufficient expertise in running these plants, e.g. to avoid an overload of the biogas system. Against this background, the anaerobic degradability of various Egyptian agricultural residues is determined by laboratory testing; this includes both a determination of degradation behavior in batch tests and a feed analysis. The residues studied produce biogas yields ranging from 303 to 496 mLN gVS -1 . Co-digestion experiments demonstrate that hardly any interaction effects occur during the fermentation process for different mixtures of the investigated residues. Based on these findings, a model is developed to estimate biogas production using the investigated agricultural residues in continuous operation and to give recommendations for the optimal mode of operation.